Overexpression of Pepper Capsaicinoid Pathway Genes in Tomato (Solanum lycopersicum L.) - Chudamani Sharma Prakash; Yi Hong Wang (European Journal of Biology)
Objective: The Solanaceae family includes many unique and popular fruits and vegetables such as potato, tomato, and pepper. Peppers are a group of plants that produce pungent fruits favoured by many in various parts of the world. This spiciness is due to a class of compounds called capsaicinoid which are synthesized in peppers but not in tomatoes. Both pepper and tomato genomes have been sequenced, and genes involved in the capsaicinoid biosynthesis pathway have been identified in both genomes. Along with expression profiling, there were only three genes in the tomato pathway that were not expressed. In this study, we attempted to overexpress the three pepper genes in tomato to produce spicy fruits. Materials and Methods: The three genes, BCAT (branched-chain amino acid aminotransferase), Kas (ketoacyl-ACP synthase), and CS/AT﻿ (capsaicin synthase/acyltransferase), were separated using P2Am and T2Am sequences in a tricistronic cassette driven by the 35S promoter. Transgenic tomato plants containing the gene construct were generated via Agrobacterium-mediated transformation. Results: RT-PCR indicated that the genes were expressed in all transgenic tomato plants. Some transgenic fruits resembled hot peppers with elongated shapes and wrinkled surfaces, but tomato fruits were not spicy based on two-person tasting evaluations. Conclusion: P2Am and T2Am sequences can be used for the overexpression of multiple genes in tomatoes. Further studies with tissue-specific promoters and metabolic profiling are necessary.